Civic-Mindedness Sustains Empathy in a Cohort of Physical Therapy Students: A Pilot Cohort Study - Palombaro, Kerstin M (J Patient Exp, 2019)
BACKGROUND: Empathy is critical to patient-centered care and thus is a valued trait in graduate health-care students. The relationship between empathy and civic-mindedness in health professions has not previously been explored. OBJECTIVES: (a) To determine whether significant differences occurred on the Jefferson Scale for Empathy–Health Professions Student Version (JSE-HPS) and Civic-Minded Professional scale (CMP) and its subscales across the curriculum, (b) to explore a potential relationship between civic-mindedness and empathy in a cohort of graduate physical therapy (PT) students at regular intervals, and (c) to explore the predictive ability of civic-mindedness on empathy scores. METHODS: This study was a convenience sample of a cohort of 48 PT students who completed both the JSE-HPS and the CMP at 4 points of a service-learning intensive curriculum. Statistical analysis included descriptive statistics, a Friedman’s analysis of variance with Wilcoxon signed-ranks post hoc testing, and Spearman correlations with stepwise linear regressions. RESULTS: Statistically significant differences were not found for the JSE-HPS. Civic-Minded Professional scores increased across the curriculum. The JSE-HPS, the CMP, and various CMP subscales were significantly correlated. The JSE-HPS pretest scores were predictive of the year 1 and 2 posttest JSE-HPS scores. CONCLUSION: This study’s findings indicate that service-learning and the resulting development of civic-mindedness supports empathy. Programs could use JSE-HPS pretests to identify individual graduate students need for empathy mentorship upon program entrance or as one admission criterion.